Research Ethics Consultation: Ethical and Professional Practice Challenges and Recommendations. (May 2015) - Sharp, Richard R.; Taylor, Holly A.; Brinich, Margaret A.; Boyle, Mary M.; Cho, Mildred; Coors, Marilyn; Danis, Marion; Havard, Molly; Magnus, David; Wilfond, Benjamin
Abstract : The complexity of biomedical research has increased considerably in the last decade, as has the pace of translational research. This complexity has generated a number of novel ethical issues for clinical investigators, institutional review boards (IRBs), and other oversight committees. In response, many academic medical centers have created formal research ethics consultation (REC) services to help clinical investigators and IRBs navigate ethical issues in biomedical research. Key functions of a REC service include assisting with research design and implementation, providing a forum for deliberative exploration of ethical issues, and supplementing regulatory oversight. As increasing numbers of academic research institutions establish REC services, there is a pressing need for consensus about the primary aims and policies that should guide these activities. Establishing clear expectations about the aims and policies of REC services is important if REC programs are to achieve their full potential. Drawing on the experiences of a Clinical and Translational Science Award Research Ethics Consultation Working Group, this article describes three major ethical and professional practice challenges associated with the provision of REC: (1) managing multiple institutional roles and responsibilities, (2) managing sensitive information, and (3) communicating with consultation requestors about how these issues are managed. The paper also presents several practical strategies for addressing these challenges and enhancing the quality of REC services.